Emergência de novos sujeitos políticos na arte contemporânea: O coletivo Nega em Florianópolis (SC, Brasil) - Raposo, P. (18th IUAES World Congress. World (of) Encounters: The Past, Present and Future of Anthropological Knowledge, 2018)
Coletivo Nega is a theatre group composed of young black women of Florianopolis (Santa Catarina) which is the capital of the State with fewer black population of Brazil. In this article I intend to examine a relatively recent phenomenon that results from a close and intense relationship between processes of identification, political and racial empowerment and political resistance with forms of protest imminently based on artistic performances. This relationship between art and politics is also visible in the way much of the contemporary artistic proposals incorporate increasingly narratives and practices that use models of autonomy, horizontality, complicity and sharing, replicating models of specific policy management from libertarian and assemblers’ movements. I seek to explore which are the emerging dimensions of embodiment and performativity entered in these bodies of people who seek racial and social visibility, strategical engagement to produce new political statements within the socio-political reality of contemporary Brazil.